Uppaal SMC tutorial - David, Alexandre; Larsen, Kim G.; Legay, Axel; Mikučionis, Marius; Poulsen, Danny Bøgsted (International journal on software tools for technology transfer, 2015)
This tutorial paper surveys the main features of Uppaal SMC, a model checking approach in Uppaal family that allows us to reason on networks of complex real-timed systems with a stochastic semantic. We demonstrate the modeling features of the tool, new verification algorithms and ways of applying them to potentially complex case studies.